Stability Analysis of Feed Gas Based on Pressure using Gas Chromatography at PT Badak NGL - Muhammad Prasha Risfi Silitonga; Feby Valentina; Reza Azhari (MBI, 2024)
As one of the LNG processing companies in Indonesia, Badak NGL plays an important role in product QA and QC. Laboratory and Environment Control PT Badak NGL obtained ISO 17025 as a testing and calibration laboratory. In clause 7.7 of ISO 17025, stated that each laboratory is required to improve competence, one of which is by holding interlaboratory meetings. Currently, PT Badak NGL is participating in the implementation of the Inter Laboratory Meeting (ILM) in East Kalimantan. In the implementation of the ILM 112th and 113th in 2022, several laboratories provide outlier results in natural gas sample testing. Various factors affect the results of natural gas sample testing, one of them is the sample pressure. This research aims to determine the minimum pressure limit in testing feed gas samples. The test is carried out by designing a series of two cylinders to test the repeatability value. The sampling process is based on GPA 2166 and the measurement of repeatability values is based on GPA 2261. This method is effective for determining the limit of repeatability values as a reference for the minimum sample pressure before being injected into Gas Chromatography.